2011
DOI: 10.1007/s11356-011-0681-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of arsenate from groundwater by electrocoagulation method

Abstract: The reported method is capable for the removal of arsenate completely (100% removal) from groundwater of Ballia district. There was no change in the groundwater quality after the removal of arsenate. The treated water was safe for drinking, bathing, and recreation purposes. Therefore, this method may be the choice of arsenate removal from natural groundwater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 162 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…It can be observed that both zinc and copper electrode assemblies attained a significant removal of arsenite. For low arsenite concentration the percentage removal was much more as compare to the solution of higher concentration (Ali et al 2012). The graph clearly indicates a sharp decrease in the percentage removal (99.89-82.92 and 99.56-78.77) for 2.0-25.0 mg/L for zinc and copper electrodes.…”
Section: Effect Of Arsenite Concentrationmentioning
confidence: 87%
“…It can be observed that both zinc and copper electrode assemblies attained a significant removal of arsenite. For low arsenite concentration the percentage removal was much more as compare to the solution of higher concentration (Ali et al 2012). The graph clearly indicates a sharp decrease in the percentage removal (99.89-82.92 and 99.56-78.77) for 2.0-25.0 mg/L for zinc and copper electrodes.…”
Section: Effect Of Arsenite Concentrationmentioning
confidence: 87%
“…Among various water treatment methods such as coagulation/flocculation (Ali et al 2012;Anjaneyulu et al 2005), precipitation (Zhu et al 2007), advanced oxidation (Azbar et al 2004), and photo-catalytic degradation (Yang et al 1998;Barka et al 2010), the adsorption process is considered to be the best method due to simplicity of design and operation, economic feasibility and reusability of adsorbents (Anjaneyulu et al 2005;Hao et al 2000;Khan et al 2015;Khan et al 2014a). The commercial activated carbon, both granular and powdered, is an excellent adsorbent for pollutants' removal from wastewater because of its high surface area and reactivity, adequate pore size/volume distribution, and relatively high mechanical strength (Khan et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…It was estimated that around 150 million people in the world are probably affected by arsenic contamination in groundwater, especially in some Asian country as China, India, and Bangladesh (Ali et al 2012). As was found in shallow tubewells in the low-lying Mekong Delta at Prey Vêng province, Cambodia.…”
Section: The Situation In the Mekong River Deltamentioning
confidence: 99%